Temperature-dependent induction of an acid-inducible stimulon of Escherichia coli in broth. - Hassani, M (1992)
The induction of the inducible lysyl-tRNA synthetase, LysU, and the inducible lysine and arginine decarboxylases of Escherichia coli K-12 grown in AC broth to a pH of 5.5 or less is temperature dependent, being distinctly lower at 24 than at 37 degrees C. This induction does not appear to be under HtpR control.